Herbicide activity al diphenylether compounds applied in post-emergence to soybeans. - Mengarda, Ildo Pedro; Fleck, Nilson Gilberto (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted during 1985/66 in the "Estação Experimental Agronômica of Universidade Federal do Rio Grande do Sul", in Guaíba, RS, Brazil, in order to evaluate the efficiency and selectivity of acifluorten, fluoroglicoten, tomesafen, and lactofen, applied at three rates and two post-emergence limes on broadleaf weed control in soybeans, and to establish the weed competition effect Application at seven days after soybeans emergence allowed high efficiency for all herbicides, even at the lowest rates, whereas application at 21 days decreased the efficiency, mainly in the lowest and the highest rates. Lactofen was the least affected by weed growth stage, promoting, in the 21 days after application, the best performance. Amaranth (Amaranthus blitum L.) was the most tolerant species to this application, followed by Brazil pusley (Richardia brasiliensis Gomez) and purslane (Portulaca oleracea L.). Dry matter evaluation of soybean seedling, sampled at seven days after applications, did not show quantitative damage by the herbicides, although visual symptoms of injury few days after applications were observed. The dicotyledonous weeds showed little competition ability, as have decreased soybean yield by an average of 12,5%.